A randomized controlled trial of financial incentives for weight loss - Volpp, Kevin G. (2008)
CONTEXT: Identifying effective strategies for treating obesity is both a clinical challenge and a public health priority due to the health consequences of obesity. OBJECTIVE: To determine whether common decision errors identified by behavioral economists such as prospect theory, loss aversion, and regret could be used to design an effective weight loss intervention. DESIGN: 3-arm randomized controlled trial in which participants were randomized to either usual care (weigh ins once a month) or one of two financial incentives arms. One incentive arm used deposit contracts in which participants put their own money at risk (matched 1:1 by the study) which they would lose if they failed to lose weight. The second used lottery-based incentives in which participants who met the weight loss target had each day a 1 in 5 chance of winning a small reward ($10) and a 1 in 100 chance of winning a large reward ($100). All participants were given a weight loss goal of 1 pound per week for 16 weeks, and results were analyzed using intention-to-treat analysis of variance models. SETTING: Philadelphia Veterans Affairs Medical Center. PATIENTS: 57 patients with BMIs between 30-40 aged between 30 and 70, with no contraindications for study participation. MAIN OUTCOME MEASURES: Weight loss after 16 weeks. RESULTS: Participants in both incentive groups lost significantly more weight than participants in the control group (3.9 pounds); (Lottery = 13.1 lbs; p-value for lottery vs. control .014; deposit contract = 14.0 lbs, p-value vs. control .003). 47.4% of deposit contract participants and 52.6% of lottery arm participants met the 16-pound weight loss goal compared to 10.5% in the control group (p-value 0.014.). By the end of 7 months, substantial amounts of weight were regained; however, incentive participants weighed significantly less than they did at the study start whereas controls did not. Low lost to follow-up rates (7.0%) during the weight loss phase of the study suggest that both incentive systems were successful in keeping participants engaged in the study. CONCLUSIONS: Incentive approaches based on behavioral economic concepts could have a major impact in reducing the incidence of obesity-related illnesses.